Accuracy of tidal volume delivered by home mechanical ventilation during mouthpiece ventilation: A bench evaluation. (November 2016) - Ogna, Adam; Prigent, Helene; Falaize, Line; Leroux, Karl; Santos, Dante; Vaugier, Isabelle; Orlikowski, David; Lofaso, Frederic
The aim of our study was to evaluate efficacy and reliability of currently available ventilators for mouthpiece ventilation (MPV). Five life-support home ventilators were assessed in a bench test using different settings simulating the specificities of MPV, such as intermittent circuit disconnection and presence of continuous leaks. The intermittent disconnection of the circuit caused relevant swings in the delivered tidal volume ( V T ), showing a V T overshoot during the disconnection periods and a V T decrease when the interface was reconnected to the test lung. The five ventilators showed substantial differences in the number of respiratory cycles necessary to reach a stable V T in the volume-controlled setting, ranging from 1.3 ± 0.6 to 7.3 ± 1.2 cycles. These differences were less accentuated in the volume-assisted setting (MPV-dedicated mode, when available). Our data show large differences in the capacity of the different ventilators to deal with the rapidly changing respiratory load features that characterize MPV, which can be further accentuated according to the used ventilator setting. The dedicated MPV modes allow improvement in the performance of ventilators only in some defined situations. This has practical consequences for the choice of the ventilator to be used for MPV in a specific patient.